2005
DOI: 10.1056/nejmra050541
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory Action of Glucocorticoids — New Mechanisms for Old Drugs

Abstract: nflammation is a reflexive response to infection, the binding of antibodies to antigens within the body, mechanical irritation, or injury. 1 Microbes that breach epithelial barriers, for instance, directly activate complement and toll-like receptors, two principal components of the innate immune system. The activation of these sentinels triggers the synthesis and release of inflammatory mediators with acute effects on the vasculature. Localized vasodilation, increased vascular permeability, extravasation of pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
1,896
5
64

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,680 publications
(2,054 citation statements)
references
References 91 publications
29
1,896
5
64
Order By: Relevance
“…In this context, potential mechanism of LPS-mediated dysfunction of adipose tissue stimulates much interest in future studies. Glucocorticoids are widely used as anti-inflammatory agents in human clinics [23]. Consistent with the notion that glucocorticoids act as anti-inflammatory hormones, our data demonstrated that treatment of J774.1 cells with dexamethasone significantly suppressed the mRNA expression and secretion of IL-1b, TNF-a and MCP-1 in a dose-dependent manner (supplementary figure).…”
Section: Discussionsupporting
confidence: 88%
“…In this context, potential mechanism of LPS-mediated dysfunction of adipose tissue stimulates much interest in future studies. Glucocorticoids are widely used as anti-inflammatory agents in human clinics [23]. Consistent with the notion that glucocorticoids act as anti-inflammatory hormones, our data demonstrated that treatment of J774.1 cells with dexamethasone significantly suppressed the mRNA expression and secretion of IL-1b, TNF-a and MCP-1 in a dose-dependent manner (supplementary figure).…”
Section: Discussionsupporting
confidence: 88%
“…Glucocorticoids represent one of the most widely used anti-inflammatory drugs (26). Their actions appear to go beyond the anti-inflammatory effects and have been shown to include inhibition of lung cancer cell growth and regulation of cell cycle (27) and chemosensitization of other cytotoxic anti-cancer drugs (28).…”
Section: Glucocorticoids Induce 15-pgdh Expressionmentioning
confidence: 99%
“…In addition, macrophages are central to tissue homeostasis in that they are involved in wound repair and tissue remodeling, secreting critical mediators like TGFβ and metalloproteinases [2,3], The properties of the macrophages are strongly influenced by GC. The effects of GC on immunological functions involves potent antiinflammatory and immunosuppressive properties [4]. The anti-inflammatory effect of GC is mediated through an inhibitory effect on proinflammatory transcription factors such as NF-KB [5], which results in reduced cytokine expression.…”
Section: Introductionmentioning
confidence: 99%